Design and Fabrication of Sensor Operated Intelligent Braking System - R. , Hariharan; Kumar, Karthik; M. , Kannan; K. , Manikandan; V. , Karthikeyan (International Journal of Psychosocial Rehabilitation, 2019)
The technology of pneumatics has gained tremendous importance in the field of workplace rationalization and automation from old-fashioned timber works and coal mines to modern machine shops and space robots. It is therefore important that technicians and engineers should have a good knowledge of pneumatic system, air operated valves and accessories. The air is compressed in an air compressor and from the compressor plant the flow medium is transmitted to the pneumatic cylinder through a well laid pipe line system. To maintain optimum efficiency of pneumatic system, it is of vital importance that pressure drop between generation and consumption of compressed air is kept very low. The aim is to design and develop a control system based an intelligent electronically controlled automotive braking system is called “AUTOMATIC REVERSE BRAKING SYSTEM”. This Braking system is consists of IR transmitter and Receiver circuit, Control Unit, Pneumatic breaking system. The IR sensor is used to detect the obstacle. There is any obstacle in the path, the IR sensor senses the obstacle and giving the control signal to the breaking system. The pneumatic breaking system is used to break the system.